Petroleum biodegrading and co-resistance to antibiotics by Serratia marcescens strain isolated in Coari, Amazonas (Acta Scientiarum. Biological Sciences, 2017)
Serratia marcescens is a Gram-negative bacillus, anaerobic facultative belonging to the family Enterobacteriaceae. S. marcescens strains are able to grow in the presence of different xenobiotic compounds, among them, petroleum and heavy metals. Xenobiotic resistant strains develop concomitant resistance to multiple antibiotics, referred to as co-resistance. The AMS212 strain was submitted to the microplate qualitative DCPIP - redox 2,6 dichlorophenol indophenol method. The quantitative test was carried out in Erlenmeyer flasks, followed by the change of color with the absorbance readings, trough the colorimetric method. The antibiotic resistance profile was evaluated by the Kirby-Bauer method. In the qualitative assay, the AMS212 strain altered the color of the DCPIP, which changed from blue to colorless, confirming that petroleum biodegradation occurred. In the quantitative test, the readings were decreasing, confirming that the concentration of DCPIP decreased as a function of the incubation time. The susceptibility test revealed that the AMS212 strain presented multiresistance to four different antibiotics. S. marcescens presented high performance in the biodegradation of petroleum, opening possibility to use it in projects involving the remediation of impacted areas. The expression of the antibiotic co-resistance phenotype confirms that the AMS212 strain is able to withstand different environmental aggressions.